Dual effect of lithium on NFAT5 activity in kidney cells - Küper, Christoph; Beck, Franz-Xaver; Neuhofer, Wolfgang (Frontiers in Physiology, 2015)
Lithium salts are used widely for treatment of bipolar and other mental disorders. Lithium therapy is accompanied frequently by renal side effects, such as nephrogenic diabetes insipidus or chronic kidney disease, but the molecular mechanisms underlying these effects are still poorly understood. In the present study we examined the effect of lithium on the activity of the osmosensitive transcriptional activator nuclear factor of activated T cells 5 (NFAT5, also known as TonEBP), which plays a key role in renal cellular osmoprotection and urinary concentrating ability. Interestingly, we found different effects of lithium on NFAT5 activity, depending on medium osmolality and incubation time. When cells were exposed to lithium for a relative short period (24 h), NFAT5 activity was significantly increased, especially under isosmotic conditions, resulting in an enhanced expression of the NFAT5 target gene heat shock protein 70 (HSP70). Further analysis revealed that the increase of NFAT5 activity depended primarily on an enhanced activity of the c-terminal transactivation domain (TAD), while NFAT5 protein abundance was largely unaffected. Enhanced activity of the TAD is probably mediated by lithium-induced inhibitory phosphorylation of glycogen synthase kinase 3b (GSK-3b), which is in accordance with previous studies. When cells were exposed to lithium for a longer period (96 h), cellular NFAT5 activity and subsequently expression of HSP70 significantly decreased under hyperosmotic conditions, due to diminished NFAT5 protein abundance, also resulting from GSK-3b inhibition. Taken together, our results provide evidence that lithium has opposing effects on NFAT5 activity, depending on environmental osmolality and exposure duration. The potential impacts of these observations on the diverse effects of lithium on kidney function are discussed.